Deficient antiviral immune responses in childhood: Distinct roles of atopy and asthma - Baraldo, Simonetta; Contoli, Marco; Bazzan, Erica; Turato, Graziella; Padovani, Anna; Marku, Brunilda; Calabrese, Fiorella; Caramori, Gaetano; Ballarin, Andrea; Snijders, Deborah; Barbato, Angelo; Saetta, Marina; et al. (Journal of allergy and clinical immunology, 2012)
Impaired immune response to viral infections in atopic asthmatic patients has been recently reported and debated. Whether this condition is present in childhood and whether it is affected by atopy per se deserves further investigation. We sought to investigate airway interferon production in response to rhinovirus infection in children who are asthmatic, atopic, or both and its correlation with the airway inflammatory profile. Bronchial biopsy specimens and epithelial cells were obtained from 47 children (mean age, 5 ± 0.5 years) undergoing bronchoscopy. The study population included asthmatic children who were either atopic or nonatopic, atopic children without asthma, and children without atopy or asthma. Rhinovirus type 16 induction of IFN-λ and IFN-β mRNA and protein levels was assessed in bronchial epithelial cell cultures. The immunoinflammatory profile was evaluated by means of immunohistochemistry in bronchial biopsy specimens. Rhinovirus type 16–induced interferon production was significantly reduced in atopic asthmatic, nonatopic asthmatic, and atopic nonasthmatic children compared with that seen in nonatopic nonasthmatic children (all P < .05). Increased rhinovirus viral RNA levels paralleled this deficient interferon induction. Additionally, IFN-λ and IFN-β induction correlated inversely with the airway TH2 immunopathologic profile (eosinophilia and IL-4 positivity: P < .05 and r = −0.38 and P < .05 and r = −0.58, respectively) and with epithelial damage (P < .05 and r = −0.55). Furthermore, total serum IgE levels correlated negatively with rhinovirus-induced IFN-λ mRNA levels (P < .05 and r = −0.41) and positively with rhinovirus viral RNA levels (P < .05 and r = 0.44). Deficient interferon responses to rhinovirus infection are present in childhood in asthmatic subjects irrespective of their atopic status and in atopic patients without asthma. These findings suggest that deficient immune responses to viral infections are not limited to patients with atopic asthma but are present in those with other TH2-oriented conditions.